Analysis and Design of an Android-Based Tourism E-Ticket Application System in The Toba Caldera with a CRM Approach - Anggun Fergina, M.Kom; Kamdan, M.Kom; Berniman Gofindo Malau (SEAN Institute, 2023)
This research aims to develop and evaluate an e-ticketing application to enhance the tourist experience at The Caldera Toba. Employing a comprehensive software development methodology, the application is designed to streamline the ticket purchasing process and improve information accessibility for tourists. Evaluation is conducted through a user satisfaction survey, measuring aspects such as usability, functionality, and application reliability. The research results indicate a high level of satisfaction among users, with a particular emphasis on user-friendliness and the efficiency of the ticket purchasing process. This study not only underscores the potential of e-ticketing applications in the tourism sector but also provides valuable insights for further development in the context of other tourist destinations. The implications of these findings are significant for stakeholders in the tourism sector, especially in efforts to enhance the tourist experience through technology.